Blockchain in Indian Healthcare - C Narwadiya, Sachin; Raghunatha Rao, Dharmapuri (Journal of Neonatal Surgery, 2025)
In the modern era of Artificial Intelligence, the healthcare industry requires advancements to ensure seamless access to treatment and diagnosis for patients. By integrating blockchain technology into the existing healthcare system, patient data can be securely stored and accessed across hospitals worldwide, transcending national boundaries. A survey to analyze the healthcare administrators, doctors, patients the use of blockchain Technology in healthcare system was conducted. The results indicated that search hits by Doctors and healthcare professionals had the positive correlation (slope = 0.4895) with a significant p-value (0.0391). Reported by healthcare professionals and projection of the utility of blockchain technology in the media reported indicated as moderate correlation. Both reports and media were statically significant. Research and News exhibited moderate correlations (approximately 0.21) and were both statistically significant (p < 0.05). In contrast, the utility of blockchain technologies in government was found to be less by showing a weaker relationship which was not statistically significant (p > 0.05).